Tabati: Tanda Baca Berbasis Kearifan Lokal Pati untuk Siswa SD Kelas I Fase A di SD 3 Terban: (Studi Kelayakan dan Kepraktisan) - Dwi Aprianti, Anggi; Nabila Pramesti, Reva; Galih Nur Rahmawati, Anggita; Setiawaty, Rani (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This research aims to develop and test the feasibility and practicality of the TABATI Application (Punctuation Based on Pati Local Wisdom) as a digital learning medium to improve understanding of the use of punctuation marks in grade I elementary school students. Methods: This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The feasibility test is carried out by material experts, media experts, and linguists, while the practicality test is obtained through the responses of teachers and students. The validation results showed that TABATI was declared suitable for use with a percentage of media expert assessment of 88%, material expert 89%, and linguist 86%. The results of the practicality test showed a very practical category, with scores of 87.65% from teachers and 93% from students. TABATI media is considered attractive, easy to use, and able to increase student involvement in learning. The novelty in this study lies in the integration of local wisdom in Pati Regency, such as barongan, baked batik, milkfish, and Rumah Joglo into reading language learning based on Android applications. This integration makes learning more contextual, meaningful, and supports the strengthening of local language and cultural literacy of elementary school students.